1987
DOI: 10.1523/jneurosci.07-09-02737.1987
|View full text |Cite
|
Sign up to set email alerts
|

Bipotential glial precursor cells of the optic nerve express the NG2 proteoglycan

Abstract: We have studied the expression of the NG2 chondroitin sulfate proteoglycan on bipotential glial precursor cells in cultures of postnatal rat optic nerve. Purified populations of these precursor cells were prepared by panning dissociated optic nerve cells on dishes coated with monoclonal A2B5 antibody. Using immunofluorescence double staining, we found that NG2 was present on almost 95% of the purified A2B5+ precursor cells. The NG2 core protein from optic nerve cells was identified by immune precipitation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
202
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(221 citation statements)
references
References 19 publications
9
202
1
Order By: Relevance
“…The antigen we have defined shows many similarities to the NG2 proteoglycan, which is also expressed by subpopulations of immature cells, including oligodendrocyte progenitor cells (Stallcup and Beasley, 1987; for review, see Levine and Nishiyama, 1996). A striking difference between the AN2 antigen and the NG2 proteoglycan is seen when the purified antigens are used as substrates for neuronal growth.…”
Section: Identity Of the An2 Antigenmentioning
confidence: 92%
“…The antigen we have defined shows many similarities to the NG2 proteoglycan, which is also expressed by subpopulations of immature cells, including oligodendrocyte progenitor cells (Stallcup and Beasley, 1987; for review, see Levine and Nishiyama, 1996). A striking difference between the AN2 antigen and the NG2 proteoglycan is seen when the purified antigens are used as substrates for neuronal growth.…”
Section: Identity Of the An2 Antigenmentioning
confidence: 92%
“…The following primary antibodies were used: m-Msi-1 (affinity-purified rabbit polyclonal antibody, used at 1:500 dilution) (Sakakibara et al, 1996); Hu proteins (mouse monoclonal IgG2B, clone 16A11, which binds to Hu proteins including HuD, HuC, and HelN-1, supplied by Dr. M. F. Marusich, University of Oregon; used at 1:500 dilution) (Marusich et al, 1994); nestin (mouse monoclonal IgG, clone RE6 -96 supplied by Dr. M. Ogawa, Kochi Medical School, Japan); ascitic fluid used at 1:1000 dilution (Miyata and Ogawa, 1994); proliferating cell nuclear antigen (PC NA) (mouse monoclonal IgG1, used at 1:200 dilution; Novocastra Laboratories); glial fibrillary acidic protein (GFAP) (mouse monoclonal IgG1, clone G-A-5, used at 1:400 dilution) (Sigma, St. L ouis, MO); 2Ј, 3Ј-cyclic nucleotide-3Ј-phosphohydrolase (C N Pase) (mouse monoclonal IgG1, clone 11-5B, used at 1:100 dilution) (Sigma); bromodeoxyuridine (BrdU) (mouse monoclonal IgG1, clone BU-33, used at 1:5000 dilution) (Sigma); MacI (mouse monoclonal IgG1, used at 1:100 dilution) (Boehringer Mannheim, Indianapolis, I N), platelet-derived growth factor ␣-receptor (PDGF␣-R) (rat monoclonal IgG, a kind gift from Dr. S.-I. Nishikawa, Kyoto University, Japan; used at 1:5000 dilution) (Takakura et al, 1996), and NG2 (mouse monoclonal IgG1, a kind gift from Dr. W. D. Richardson, University College L ondon, UK ; used at 1:100 dilution) (Stallcup and Beasley, 1987). Secondary and tertiary reagents were obtained commercially from Vector Laboratories (Burlingame, CA) or Jackson ImmunoResearch (West Grove, PA).…”
Section: Methodsmentioning
confidence: 99%
“…PDGF␣-R is expressed in the developing and adult rodent CNS by the O-2A oligodendrocyte progenitors and preoligodendrocytes (Pringle et al, 1992;Ellison and de Vellis, 1994;Nishiyama et al, 1996). Similarly, NG2, a core membrane protein associated with chondroitin sulfate proteoglycan, is also expressed in mitotic O-2A progenitor cells localized in the gray and white matter of perinatal to adult rat brain and disappears as these cells differentiate into oligodendrocytes (Stallcup and Beasley, 1987;Nishiyama et al, 1996). Although the majority of NG2-positive cells also express PDGF␣-R, a recent detailed immunohistochemical comparison of the expression of PDGF␣-R and NG2 throughout CNS development demonstrated that the small population of the PDGF␣-R-positive NG2-negative cells lies in the SVZ through the first postnatal week (Nishiyama et al, 1996).…”
Section: T He White Mattermentioning
confidence: 99%
“…Studies on experimental glioma using the RCAS/tv-a model have shown that neural/glial stem cells in Ntv-a mice and neural stem cells/astrocytes in Gtv-a mice have the capacity to generate gliomas Holland and Vermus, 1998). The majority of induced tumors in both Ntv-a and Gtv-a mice were positive for NG2 chondroitin sulfate proteoglycan (NG2), a marker of early oligodendrocyte progenitor cells (OPCs) (Stallcup and Beasley, 1987;Pringle and Richardson, 1993;Nishiyama et al, 1996;Polito and Reynolds, 2005). This implied that the OPCs could represent the optimal level of cellular differentiation for oncogenic transformation to occur.…”
Section: Introductionmentioning
confidence: 99%